Pemberdayaan UMKM Melalui Rebranding, Legalitas, dan Digitalisasi: Studi Kasus Program Level Up UMKM di Desa Banyuresmi, Tasikmalaya: Pengabdian - Alfin nur Arifah; Ghina Nishfy Sya’bani; Aida Siti Nurmalia; Fajar Septiana; Adi Nugraha; Muhammad Riski Triana; Habib Haedar; Sri Indri Oktavian; Nabila Luthfiyyah; Nadia Angraeni; Adinda Kustiani; Sindy Kania Suryani; Sinta Khoerunnisa; Abdul Aziz Kelinsman; Anisa Putri Maharani; Muhammad Khoerulrijjal Salsabila J; Syifa Aenun Naja; Muhamad Amirul Rizki; Ikbal Maulana; Vanesa Selyandra (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The objective of this Community Service Program is to to empower MSMEs in Banyuresmi Village through strengthening rebranding, legality, and digitalization to enhance business competitiveness and sustainability in the Industry 4.0 era. The community service activity employed a participatory approach involving 28 selected MSMEs from 62 registered MSMEs based on business sustainability criteria and willingness to participate in the mentoring program. The implementation method was divided into three stages: (1) planning and problem identification through field observations, discussions with MSME owners and village officials, and needs analysis; (2) education and training on the importance of branding, business legality (NIB, PIRT, Halal certification), and digital media utilization; and (3) implementation and direct mentoring, including logo design, brand development, packaging, digital promotion, and facilitation of legality arrangements in collaboration with relevant agencies. The results indicated that prior to the program, approximately 90% of MSMEs lacked brand identity, only 15% possessed business legality, and 85% had not utilized digital marketing. Following the mentoring program, the majority of MSMEs acquired logos and simple packaging, approximately 85% successfully obtained NIB (Business Identification Number), and most began actively using social media as promotional platforms. These findings indicate that the integration of rebranding, legality, and digitalization through a participatory approach constitutes an effective empowerment strategy for strengthening the capacity and competitiveness of rural MSMEs.